2011
DOI: 10.1039/c1nr10141b
|View full text |Cite
|
Sign up to set email alerts
|

Role of spacer lengths of gemini surfactants in the synthesis of silver nanorods in micellar media

Abstract: In this work, we have prepared Ag-nanorods using biscationic gemini surfactant micelles as the media by a seed-mediated wet synthesis method. Towards this end, we first synthesized Ag-nanoseeds of diameter ~7 nm stabilized by trisodium citrate (as the capping agent). Then these Ag-nanoseeds were used to synthesize Ag-nanorods of different aspect ratios. With decreasing Ag-nanoseed concentration, the aspect ratios of the Ag-nanorods stabilized by these gemini surfactants increased gradually. Various Ag-nanoseed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…From the seed-mediated synthesis of Ag-nanorods in the geminies Bhattacharya and Biswas [67] observed that the growth of the rods which was inversely proportional to the length of spacer. Das et al [71] reported the role of the SDS micelles in the formation of the GNPs in aqueous solution.…”
Section: Characterization Of Gnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the seed-mediated synthesis of Ag-nanorods in the geminies Bhattacharya and Biswas [67] observed that the growth of the rods which was inversely proportional to the length of spacer. Das et al [71] reported the role of the SDS micelles in the formation of the GNPs in aqueous solution.…”
Section: Characterization Of Gnpsmentioning
confidence: 99%
“…Surfactants can play an important role in the synthesis and stabilization of metal nanoparticles (NP); they can as well control the size and shape of the NPs depending on their types and lengths [67][68][69][70][71][72]. Cationic surfactants have potential effect on the above process.…”
Section: Characterization Of Gnpsmentioning
confidence: 99%
“…In addition, ammonium based gemini surfactants have remarkable role in aggregation and displaying rate acceleration involving in chemical reactions as compared to the conventional single chainsingle headgroup surfactants [9][10][11][12][13][14]. It is already known that the spacer group of the gemini surfactant plays an important role for the synthesis of Au and Ag nanoparticles (NPs) and significantly controls their size and shape [9,10,15].…”
Section: Introductionmentioning
confidence: 99%
“…It is already known that the spacer group of the gemini surfactant plays an important role for the synthesis of Au and Ag nanoparticles (NPs) and significantly controls their size and shape [9,10,15]. Yao and co-workers [10] have reported the formation of well separated spherical Au-NPs of different size in aqueous medium using alkanediyl-a,x-bis http://dx.doi.org/10.1016/j.jcis.2014.12.064 0021-9797/Ó 2014 Elsevier Inc. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, usually surfactants prefer to attach on the (100) facet rather than (111) facet, which leads to an ordered anisotropic growth to produce nanorods particle [39,40]. Crystallography of Fe3O4 naanoparticles are inverse-spinel crystal with face-centered cubic, structures (Fd3m space group) [41].…”
Section: Proposed Formation Mechanism Of Nanoparticles With Differentmentioning
confidence: 99%